Ion-channel Modulator: Panacea against Diabetic and Nicotine-induced Cataract - Chidrawar, Vijay R.; Shiromwar, Shruti; Aljameeli, Ahmed M.; Vattikutti, Uma Maheshwararao (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
Introduction: Ion-channels are the pore-forming proteins that bridge across the cell membrane and selectively conduct the ions on either side of the membrane. Inorganic ions like Na+, K+, Ca++, and Cl– play a chief role in the maintenance of lens hydration and transmittance. In uncontrolled diabetes, cigarette smoking is considered a major risk factor for the development of cataracts. Smoking nicotine-containing cigarettes aggravate cataract formation by disturbing the normal lens physiology via disturbing the ionic balance across the lens epithelium, and the generation of free radicals. Based on this understanding we screened a few drugs like lidocaine (as Na+ and K+ channels blocker), nifedipine (a calcium antagonist), and phenylglycine against the streptozotocin (STZ) + nicotine-induced cataract model. Methodology: Diabetic contract due to nicotine aggression was induced in the rats by using STZ and nicotine. By administrating a combination of STZ (single dose of 52 mg/kg i.p.) and nicotine (0.3 mg/kg s.c.to a maximum dose of 2.1 mg/kg) for 22 consecutive days and simultaneously treated with ophthalmic preparation of test drug i.e., lidocaine, nifedipine, and phenylglycine at 1% and 2% concentration to the right and left eye respectively. On the 23rd day of the study, various parameters like measurement of various ions (Na+, K+, Ca++, and Cl–), anti-oxidants (ascorbic acid, sulfhydryl, and glutathione), and fructose content in rat lens were studied. We also investigated the level of ascorbic acid in serum and monitored the blood glucose level at regular intervals throughout the experiment. Results: Lens opacity was observed in the negative control groups in all animals. This is due to the malfunctioning of the Na+-K+-ATPase pump due to fructose accumulation leads to the accumulation of Na+ ions inside the membrane and eventually results in the accretion of water and osmotic swelling of the lens. Not all the test drugs have shown a protective effect but the treatment of lidocaine in both concentrations i.e., 1% (right eye) and 2% (left eye) significantly (P<0.001) reduced the Na+ levels, in a dose-dependent manner as compared to the disease control group. Conclusion: In the present study, nifedipine has not offered any protection while phenylglycine has shown moderate protection in a few of the study parameters. Lidocaine has offered the best protection against nicotine + diabetes-induced cataracts due to its anti-oxidant and Na+ channel blocking property.